Aggressive placement of distal limb perfusion catheter in venoarterial extracorporeal membrane oxygenation. Issue 12 (December 2020) - Ohira, Suguru; Kawamura, Masashi; Ahern, Kristin; Cavarocchi, Nicholas; Hirose, Hitoshi
Objective: The aim of this study is to review the impacts of aggressive placement of a distal perfusion catheter on the outcomes in patients supported with venoarterial extracorporeal membrane oxygenation via femoral cannulation. Methods: Analysis was performed with 143 consecutive femoral venoarterial extracorporeal membrane oxygenation cannulation. Patients were divided into two groups: the early period (October 2010 to December 2012, N  = 47) where placement of a distal perfusion catheter was attempted percutaneously but not surgically and the late period (January 2013 to November 2018, N  = 96) in which placement of distal perfusion catheter was aggressively utilized both percutaneously and surgically. The modification of venoarterial extracorporeal membrane oxygenation cannulation protocol for the late period involved (1) an immediate insertion of a distal perfusion catheter regardless of the size of femoral arterial cannula, (2) an open insertion of a distal perfusion catheter if percutaneous approach failed, and (3) when venoarterial extracorporeal membrane oxygenation cannulation was completed at a non-extracorporeal membrane oxygenation cannulation center, it was encouraged that they attempt insertion of a distal perfusion catheter at the time of cannulation. Results: In the late period, a distal perfusion catheter was placed in 96% (92/96) which was significantly increased from 66% (31/47) in the early period. Of these 92 patients in late period, nine patients (9.8%) required open direct insertion of a distal perfusion catheter. The incidence of lower limb ischemia (early vs. late period 26% vs 12%, P  = 0.031) was significantly decreased in the late period. Logistic regression analyses showed that distal perfusion catheter placement was the only factor for preventing lower limb ischemia. Conclusion: Aggressive insertion of a distal perfusion catheter even utilizing surgical cut-down technique was shown to decrease the incidence of distal limb complications.